A new direct allylation of the aromatic compounds with allylic chlorides catalyzed by indium metal - Lim, HJ; Keum, GC; Kang, SB; Kim, YS; Chung, BY (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
A new method of the direct allylation reaction for the aromatic compounds with allylic chlorides using a catalytic amount of indium in the presence of CaCO3/4 Angstrom molecular sieves was developed, (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: FRIEDEL-CRAFTS ALKYLATIONS; FUNCTIONAL SELECTIVITY; REAGENTS